2016
DOI: 10.1038/srep25755
|View full text |Cite
|
Sign up to set email alerts
|

An integrated soil-crop system model for water and nitrogen management in North China

Abstract: An integrated model WHCNS (soil Water Heat Carbon Nitrogen Simulator) was developed to assess water and nitrogen (N) management in North China. It included five main modules: soil water, soil temperature, soil carbon (C), soil N, and crop growth. The model integrated some features of several widely used crop and soil models, and some modifications were made in order to apply the WHCNS model under the complex conditions of intensive cropping systems in North China. The WHCNS model was evaluated using an open ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 50 publications
2
31
0
1
Order By: Relevance
“…Field evidence has shown that proper nutrient management during rice production can improve crop yield while reducing the N application rate and decreasing the environmental costs through integrated soil-crop system management (ISSM) 4, 15 . Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Field evidence has shown that proper nutrient management during rice production can improve crop yield while reducing the N application rate and decreasing the environmental costs through integrated soil-crop system management (ISSM) 4, 15 . Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The crop modeling analyses showed that cereal crops are most vulnerable to increasing water scarcity in many countries of the world [29]. Recently, an integrated soil-crop model (WHCNS, soil water-heat-carbon-nitrogen simulator) was developed based on the Chinese climate, soil types, and field management and the model has been successfully applied to simulate water use, N loss, and N use efficiency in China [30][31][32]. Previous research showed that the model simulated soil and crop indicators agreed well with observed data [33].…”
mentioning
confidence: 99%
“…For example, the CENTURY/DAYCENT model (Parton et al 1988(Parton et al , 1998 focuses on carbon and nutrient dynamics and has been widely accepted by the ecological and geochemical communities, though they do not use physically based equations to calculate data. Liang et al (2016) developed an integrated soil-crop system model called Soil Water Heat Carbon Nitrogen Simulator, containing modules to model soil water, soil temperature, soil carbon, soil nitrogen, and crop growth in North China. It has been integrated with various root growth models (Groenendyk et al 2012;Peña-Haro et al 2012;Zhou et al 2012;Li et al 2014;Han et al 2015;Hartmann et al 2018).…”
Section: Definition and Scopementioning
confidence: 99%
“…It has been integrated with various root growth models (Groenendyk et al 2012;Peña-Haro et al 2012;Zhou et al 2012;Li et al 2014;Han et al 2015;Hartmann et al 2018). Liang et al (2016) developed an integrated soil-crop system model called Soil Water Heat Carbon Nitrogen Simulator, containing modules to model soil water, soil temperature, soil carbon, soil nitrogen, and crop growth in North China. A DSSAT-HYDRUS 1D coupling was tested to simulate soil water dynamics along with crop growth and yield in Florida, USA (Shelia et al 2018).…”
Section: Definition and Scopementioning
confidence: 99%
See 1 more Smart Citation